THE SPELLING OF JOINT NOUNS, WHICH IS WRITTEN SEPARATELY IN THE CURRENT KARAKALPAK LANGUAGE - Opaeva Raygul Aymanovna (Galaxy International Interdisciplinary Research Journal, 2021)
Writing is the necessity of the development of language, the expansion of its social function, the result of human experience arising from the demands of life. The emergence, formation and development of any literary language is related to writing. Spelling of compound words is done in two different ways, first, by the lexemation of word combinations; second, it is known to be made by the method of adding words (composition).